Analisis Perencanaan Break Water Dalam Penanganan Sedimentasi Pantai Di Desa Botubarani - Ilyas Ichsan; Abdul Haris Suleman (Gorontalo Journal of Infrastructure and Science Engineering, 2018)
Botubarani Beach is a coastal tourist attraction that has activities that can stimulate economic growth for people who are on the coast. Research and identification of the handling of natural phenomena in the shoreline is needed to provide the right handling solution in order to avoid increasing the level of more severe damage. The purpose of this study is to analyze and plan the types and dimensions of the right coastal protection building at Botubarani Beach. Beach buildings are used to protect the coast against damage caused by wave and current attacks. Coastal buildings are classified into three groups according to their function, ie construction constructed on shore and parallel to the shoreline (revetment), constructed on a straight coastal and coastal (groin and jetty) constructions constructed offshore and approximately parallel to the coastline (breakwater). The results of data analysis and calculation found that the building that will be used to handle sedimentation in Botubarani Beach is a break water building with the type of building that is rubble mount. Plate water level elevation is 1,694 m and for selected tetrapod protected layer.